Kebijakan Harga Pembelian Gabah Pemerintah: Analisis Dua Rezim Politik di Indonesia - Heryanto, Mahra Arari; Kurnia, Ganjar (Universitas Galuh, 2025)
The Government Purchasing Price (HPP) is a key policy instrument for stabilizing food prices in Indonesia, particularly aimed at ensuring farm-level income by regulating the price of Dry Harvested Unhusked Rice (GKP). However, its effectiveness in influencing GKP prices remains underexplored across different administrations and over time. This study applies a quantitative approach using multiple linear regression analysis based on monthly data from January 2008 to November 2024. The models compare two presidential periods: President SBY (2008–2014) and President Jokowi (2014–2024). Independent variables include time (in months), HPP, and the input price index paid by farmers. The regression results show that during the SBY administration, HPP had no significant effect on GKP prices, although GKP prices consistently increased over time. In contrast, during Jokowi’s administration, HPP significantly and positively affected GKP prices, yet time trends indicated a declining price pattern. Moreover, increases in input costs strongly influenced the rise in GKP, suggesting that price gains did not necessarily translate to improved farmer welfare. Under SBY, HPP served more as a price floor in a relatively stable market. Under Jokowi, although more active, the HPP was overshadowed by escalating production costs. Therefore, HPP’s effectiveness in enhancing farmer welfare depends on its integration with input cost policies, infrastructure support, and adaptive market interventions.